3D-printed functional electrodes towards Zn-Air batteries. (June 2020) - Zhang, Jian; Li, Xue Liang; Fan, Shuang; Huang, Shaozhuan; Yan, Dong; Liu, Lei; Valdivia y Alvarado, Pablo; Yang, Hui Ying
Abstract: Fabrication and assembly of electrodes are of great importance for the manufacturing of batteries, which are the bridge to transfer electrode materials to devices. Here, we demonstrate a 3D-printing technology for the construction of functional electrodes (including anode and cathode) for zinc-air batteries. The printed anode consists of many zinc micro-spheres that allows the high utilization of the zinc. The printed self-standing air cathode features hierarchical porous structure with high surface area, which endows the electrode with high electrocatalytic activity and fast diffusion channel for the reaction. Benefiting from these advantages, the as-assembled zinc-air batteries achieve a high discharge capacity of 670 mA h g −1 at the current density of 5 mA cm −2, and long-term cycle stability at least 350 cycles, which are superior to those of conventional batteries. The reasons behind these properties and their respective characteristics are well explored and clarified. This work successfully validates the feasibility of printing battery electrodes, which might revolutionize battery manufacturing. Highlights: 3D-printing technology is used to construct functional electrodes. Zinc-air batteries electrodes are printed. The printed zinc-air batteries superior performance. Successfully validates the feasibility of printing battery electrodes, which might revolutionize battery manufacturing.